Middle managers’ sensemaking practices in developing strategic consensus - Tram, Nguyen (My University, 2026)
Organizational performance depends on both effective formulation and implementation of strategies. The strategic management research has traditionally emphasized formulation, but implementation remains comparatively underexplored, and many organizations continue to struggle to translate strategic intent into coordinated actions. Strategic consensus, defined as shared understanding and commitment to strategic priorities across organizational levels, has been identified as a critical factor for implementation success. However, achieving such consen sus is challenging, particularly in complex and ambiguous environments. Middle managers oc cupy an important position between top management and frontline employees and play a cen tral role in interpreting, translating, communicating, and aligning strategic intent across organi zational levels. Although prior research has separately examined strategic consensus, sensemak ing, and middle managers’ roles in strategy implementation, limited studies have integrated these streams to explain how middle managers actively construct shared understanding and commitment as a socially embedded process during strategy implementation. This thesis, there fore, aims to explore how middle managers develop strategic consensus through sensemaking to enhance strategy implementation effectiveness. Specifically, it seeks to uncover the pro cesses through which middle managers interpret strategic intentions, translate and communi cate strategic meanings, and align understanding and commitment across organizational levels during implementation. This study adopted a qualitative multiple-case study research design and conducted semi-structured interviews with five middle managers in the Vietnamese life in surance industry. Data were analysed using the Gioia methodology to systematically develop higher-level theoretical dimensions from the interviewees’ descriptions of their experiences. The findings show that middle managers construct strategic consensus through six interrelated sensemaking practices: interpreting strategic intentions, translating and communicating mean ings, aligning understanding and commitment, navigating structural and political dynamics, managing the emotional dynamics of change, and leveraging organizational culture. Strategic consensus emerges as a dynamic and continuously reconstructed outcome of ongoing interpre tive, structural, emotional, and relational work. By integrating these dimensions into a coherent process model, the study extends theoretical insights into the underlying process of strategy implementation while offering practical guidance on how organizations can enable middle man agers to sustain alignment, coordination, and commitment throughout strategic change.
Keywords: strategic leadership; middle management; committing oneself; strategic planning; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development